Smart steering auto alert system - Abdul Muin, Mohd Fahmi; Za'bah, Nor Farahidah (Institute of Electrical and Electronics Engineers Inc., 2018)
Drivers can easily be distracted by their handheld devices while they are driving and this ultimately contributed to the increase of road accidents. This work proposed a steering wheel cover that is designed using an array of touch sensors TTP223 and Raspberry Pi 3 microprocessor. A tilt sensor is also incorporated in order to mimic the movement of the system. Using Python as the main programming language and the Raspbian OS, for a sample size of 40 touch inputs, the system yielded an accuracy of 97.5 % and 75.0 % in its input detection during stationary and driving mode. The results have shown that as a proof of concept, the proposed system is capable of detecting touch inputs from the user’s hand and determining the position of the hands on the steering wheel.